Clinical and genetical aspects of autosomal dominantly inherited osteogenesis imperfecta tarda - László, Aranka (Acta Biologica Szegediensis, 2003)
Osteogenesis imperfecta (OI) tarda dominant type is caused by mutations in the type I collagen genes, COL1A1 and COL1A2. The essence of our haplotype analysis of osteogenesis imperfecta (OI) was to get information about the value of 8 short tandem repeat (STR) markers for the segregation of COL1A1 and COL1A2 genes on the 12 OI pedigrees and to delimit the place of mutation to one locus. The molecular genetic analysis supported the linkage to COL1A1 gene in 6 families, and in 4 families with type I B, and in one family with type III B the linkage to COL1A2 gene was supported. One patient had type IV A, where linkage to COL1A1 gene had been excluded, and haplotype analysis for COL1A2 was non conclusive in six families. As both genes consist of more than 50 exons, the haplotype analysis is very important before direct mutation screening. To achieve the maximum theoretical LOD scores for the haplotype analysis, more STR markers are needed as in many cases our markers were non informative.